Nintedanib in an elderly non-small-cell lung cancer patient with severe steroid-refractory checkpoint inhibitor-related pneumonitis: A case report and literature review - Pan, Lei; Meng, Fanqi; Wang, Wei; Wang, Xu-hao; Shen, Hui; Bao, Pengchen; Kang, Jian; Kong, Delei (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs) tremendously improved the cancer prognosis while severe grade immune-related adverse events (irAEs) might cause premature death. Current recommendations towards checkpoint inhibitor-related pneumonitis (CIP) treatment are mainly about immunosuppressive therapy while anti-fibrotic agents are also needed especially for those patients with poor response to corticosteroids and longer pneumonitis course as fibrotic changes also take an important part in the pathological evolution process of CIP. Here we report a case to introduce nintedanib is a promising candidate drug in CIP management or even prevention as it has potent anti-fibrotic efficacy and a safety profile. Moreover, nintedanib could partially inhibit tumor growth on non-small cell lung cancer (NSCLC) patients but better in combination with other anti-tumor therapy.